2011
DOI: 10.1074/jbc.m111.239673
|View full text |Cite
|
Sign up to set email alerts
|

The LptD Chaperone LptE Is Not Directly Involved in Lipopolysaccharide Transport in Neisseria meningitidis

Abstract: The biosynthesis of lipopolysaccharide (LPS) in Gram-negative bacteria is well understood, in contrast to the transport to its destination, the outer leaflet of the outer membrane. In Escherichia coli, synthesis and transport of LPS are essential processes. Neisseria meningitidis, conversely, can survive without LPS and tolerates inactivation of genes involved in LPS synthesis and transport. Here, we analyzed whether the LptA, LptB, LptC, LptE, LptF, and LptG proteins, recently implicated in LPS transport in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 46 publications
(54 reference statements)
8
45
0
Order By: Relevance
“…We found that this gene cluster is largely conserved among Gram-negative bacteria in the gene composition and order and homology of protein sequences, indicating common functions of these genes. A recent report showed that the Neisseria meningitidis LptC orthologue is involved in LPS transport and the disruption of N. meningitidis lptC and other Lpt genes reduced cellular LPS (Bos & Tommassen, 2011). However, the specific effect of Lpt disruption on LPS biosynthesis was not clear.…”
Section: Discussionmentioning
confidence: 98%
“…We found that this gene cluster is largely conserved among Gram-negative bacteria in the gene composition and order and homology of protein sequences, indicating common functions of these genes. A recent report showed that the Neisseria meningitidis LptC orthologue is involved in LPS transport and the disruption of N. meningitidis lptC and other Lpt genes reduced cellular LPS (Bos & Tommassen, 2011). However, the specific effect of Lpt disruption on LPS biosynthesis was not clear.…”
Section: Discussionmentioning
confidence: 98%
“…1C). Increased protein levels in spent medium can also be diagnostic for periplasmic leakage, a process observed in mutants deficient in LPS biosynthesis or transport (22) or in strains depleted for essential Bam complex components such as ComL, the BamD homolog in N. meningitidis (11). The extracellular protein profile of the ⌬GNA2091 mutant showed bands characteristic of both a ComL-depleted strain and a ⌬rmpM mutant (Fig.…”
Section: A Gna2091 Deletion Mutant Displays Major Defects Inmentioning
confidence: 99%
“…Hence, we first considered the possibility that GNA2091 is involved in LPS transport. To address this possibility, we analyzed cellular LPS levels because defects in LPS transport in N. meningitidis lead to a feedback inhibition on LPS synthesis (1,22). SDS-PAGE analysis, however, revealed similar LPS levels in parent and mutant cells ( Fig.…”
Section: A Gna2091 Deletion Mutant Displays Major Defects Inmentioning
confidence: 99%
“…The expected loci for the two remaining periplasmic Lpt components (LptC and LptE) encode proteins sharing minor domain characteristics with their E. coli counterparts. 13 Interestingly, the proteins encoded in these H. pylori loci are found across Epsilonproteobacteria, suggesting that this class of bacteria may contain unique conserved functional equivalents to E. coli LptC and LptE proteins. 13 Finally, H. pylori does contain a strong homolog of LptD, which delivers LPS to the outer leaflet of the outer membrane, completing the transport process.…”
Section: Synthesis and Transportmentioning
confidence: 99%
“…13 Interestingly, the proteins encoded in these H. pylori loci are found across Epsilonproteobacteria, suggesting that this class of bacteria may contain unique conserved functional equivalents to E. coli LptC and LptE proteins. 13 Finally, H. pylori does contain a strong homolog of LptD, which delivers LPS to the outer leaflet of the outer membrane, completing the transport process. All in all, H. pylori seems to possess most of the machinery that E. coli uses to transport LPS, though genetic loci, sequence, and structure of several proteins are not perfectly conserved.…”
Section: Synthesis and Transportmentioning
confidence: 99%